2019
DOI: 10.1016/j.yhbeh.2018.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific effects of aromatase inhibition on the activation of male sexual behavior in male Japanese quail (Coturnix japonica)

Abstract: Aromatization within the medial preoptic nucleus (POM) is essential for the expression of male copulatory behavior in Japanese quail. However, several nuclei within the social behavior network (SBN) also express aromatase. Whether aromatase in these loci participates in the behavioral activation is not known. Castrated male Japanese quail were implanted with 2 subcutaneous Silastic capsules filled with crystalline testosterone and with bilateral stereotaxic implants filled with the aromatase inhibitor Vorozole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 99 publications
4
22
0
Order By: Relevance
“…In the Japanese quail, courtship behavior and mating was impaired by the administration of an aromatase inhibitor (Balthazart, Foidart, & Hendrick, 1990; Watson & Adkins‐Regan, 1989). In addition, de Bournonvillea, Vandriesa, Ball, Balthazart and Cornil (2019) reported that the production of E in the POA has been shown to play a critical role in the long‐term control of male reproductive behavior in male Japanese quail. Placement of E in the medial POA of rats was found to facilitate copulatory behavior (Clancy, Zumpe, & Michael, 2000; Vagell & McGinnis, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In the Japanese quail, courtship behavior and mating was impaired by the administration of an aromatase inhibitor (Balthazart, Foidart, & Hendrick, 1990; Watson & Adkins‐Regan, 1989). In addition, de Bournonvillea, Vandriesa, Ball, Balthazart and Cornil (2019) reported that the production of E in the POA has been shown to play a critical role in the long‐term control of male reproductive behavior in male Japanese quail. Placement of E in the medial POA of rats was found to facilitate copulatory behavior (Clancy, Zumpe, & Michael, 2000; Vagell & McGinnis, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study 27 and post‐mortem histological analyses performed after preliminary experiments had shown that, when using a c‐c distance of 1.5 mm, the cannula tips were located laterally to the POM, questioning whether the drug could efficiently diffuse to the targeted nucleus. Therefore, in experiment 1 we used two types of bilateral cannulas with c‐c distances of 1.5 or 0.8 mm.…”
Section: Methodsmentioning
confidence: 97%
“…Cannulas were filled by tapping 30 times the cannula tips into crystalline VOR or CHOL filling the cannula with approximatively 1 mm length powder. The inhibitor packed in the cannula diffuses slowly into the brain areas immediately adjacent to the cannula tip and this technique was shown to successfully inhibit male quail copulatory behaviour for several weeks in previous studies 26,27 …”
Section: Methodsmentioning
confidence: 99%
“…As to the nature of this change, it is noteworthy that in Ar.X, and to a lesser degree lMAN, amylin mRNA levels were especially higher in incubating and feeding males as opposed to females but no such difference was evident in the flocked (unpaired) birds. It is well established that vocalisation changes after pair formation (D'Amelio et al, 2017). Acoustic communication ceases to function as a sexual display and becomes an agent for coordination of behaviour required for biparental care (Boucaud et al, 2017).…”
Section: Sexually Dimorphic Expression Of Amylin In the Song System Smentioning
confidence: 99%
“…While social brain networks have been suggested to be well conserved during evolution (O'Connell and Hofmann, 2011;Young et al, 2019) suggesting similar brain mechanisms in birds and mammals, our knowledge on parental control in birds is limited. The preoptic area in various bird species has been shown to be involved in male sexual behaviours (Merullo et al, 2018;de Bournonville et al, 2019), social stimulus recognition (Lorenzi et al, 2017) and parental care (Slawski and Buntin, 1995;Ruscio and Adkins-Regan, 2004). The expression of amylin, a peptide showing 80% identity to the human amylin (Fan et al, 1994), has been reported in the brain of chicken using RT-PCR (Remes et al, 2015) and Northern blotting (Fan et al, 1994).…”
mentioning
confidence: 99%